Factores determinantes de la respuesta insulínica en sujetos con pruebas normales de tolerancia oral a la glucosa - Villeno Chávez, Jaime (2001)
Insulin resistance (IR) has been associated to the plurimetabolic syndrome, a know risk factor for coronary heart disease. Fasting plasma insulin and the 120 minutes insulin response to an oral glucose tolerance test (OGTT), are both widely used in clinical practice and indirectly estimate IR. The aim of this study is to determine insulin levels in our population, both fasting and at 2 hours after 75 g oral glucose load, and the factors conditioning them. 92 normotensives subjects (65 females), aged 42.1 ± 13.9 years, with a mean body mass index (BMI) of 31.8 ± 7.6 kg/m² and whit normal OGTT (WHO 1997) were studied. Median of serum fasting  insulin and the values of the upper (UQ) and lower quartiles (LQ) were; 11.85 uU/ml (26.3-93.3). Grouping subjects by the BMI, as normal, overweight and o base (WHO 1997), the median of the basal insulin and the UQ and LQ values were 6.6 (5.6-8.7), 11.5 (7.4-34.5) and 16.3 (9.4-27.4), respectively (p<0.00001) and after 120 minutes post glucose oral load were: 31.5 (19.2-34.4), 76.5 (30.1-76.8) and 96.9 (35.8-138) (p<0.00001). there was no difference in basal or 120 minutes insulin, nor by sex, neither by diabetic antecedent  in relatives. Basal insulin correlated significantly with weight (r=0.52), BMI (r=0.57), waist circumference (WC) and triglycerides (r=0.469). multiple regression analysis disclosed BMI as the only variable related to basal insulin (p<0.0212). Insulin after 120 minutes glucose loas correlated significantly with basal insulin (r=0.339) and triglycerides (r=0.36). Multiple regression analysis and showed basal independently related to it (p<0.00001).